2021
DOI: 10.1002/joc.7058
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal patterns of ENSO‐precipitation relationships in the tropical Andes of southern Peru and Bolivia

Abstract: Precipitation is vital in the outer tropical Andes, regulating freshwater availability, flooding, glacier mass balance, and droughts. Precipitation in the region, however, is highly seasonal and exhibits considerable interannual variability. The primary driver in interannual variability is the El Niño Southern Oscillation (ENSO), with most investigations reporting that the El Niño (La Niña) results in negative (positive) precipitation anomalies across the region. Recent investigations, however, have identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…Fluctuations in ENSO between warm (El Niño) and cold (La Niña) phases are the main drivers of interannual precipitation and air temperature variability across South America (Garreaud et al, 2009). However, the influence of ENSO on precipitation in Peru varies between the north and south of the country, with distance from the Amazon and according to the El Niño regime (Jonaitis et al, 2021;Lavado-Casimiro & Espinoza, 2014;Sanabria et al, 2018). At Shallap, Maussion et al (2015) found a strong anticorrelation between glacier mass balance and ENSO, with El Niño years associated with reduced snowfall and increased net shortwave radiation, which generally agrees with the results for Artesonraju (Section 5.5).…”
Section: What Are the Key Drivers Of The Energy And Mass Balance Of Peruvian Glaciers?supporting
confidence: 82%
See 2 more Smart Citations
“…Fluctuations in ENSO between warm (El Niño) and cold (La Niña) phases are the main drivers of interannual precipitation and air temperature variability across South America (Garreaud et al, 2009). However, the influence of ENSO on precipitation in Peru varies between the north and south of the country, with distance from the Amazon and according to the El Niño regime (Jonaitis et al, 2021;Lavado-Casimiro & Espinoza, 2014;Sanabria et al, 2018). At Shallap, Maussion et al (2015) found a strong anticorrelation between glacier mass balance and ENSO, with El Niño years associated with reduced snowfall and increased net shortwave radiation, which generally agrees with the results for Artesonraju (Section 5.5).…”
Section: What Are the Key Drivers Of The Energy And Mass Balance Of Peruvian Glaciers?supporting
confidence: 82%
“…El Niño (La Niña) episodes are characterized by anomalously warm (cold) temperatures, which increase (decrease) ablation across the tropical Andes (Francou et al., 2004; Maussion et al., 2015; Thompson et al., 2017). However, the effect of ENSO fluctuations on precipitation is spatially variable across Peru, with the sign of precipitation change varying with latitude, El Niño regime, and in southern Peru, with distance to the Amazon (Jonaitis et al., 2021; Lavado‐Casimiro & Espinoza, 2014; Sanabria et al., 2018)…”
Section: Regional Climate and Glacier Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in the Introduction, the ENSO is a dominant teleconnection to central Andean climate with a complex response over the high terrain of the Altiplano (e.g., Jonaitis et al., 2021; Vuille et al., 2000). Below we map ENSO correlations from each reanalysis to the large‐scale South America domain using two approaches.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Jonaitis et al. (2021) show from 75 observational records above 2,500 m a.s.l. that El Niño (La Niña) elicits wet‐season (December–February) precipitation deficits (surpluses) across the eastern and northeastern Altiplano, while El Niño or ENSO‐neutral conditions bring precipitation surpluses to the west.…”
Section: Introductionmentioning
confidence: 99%